Producing Knowledge about Racial Differences: Tracing Scientists' Use of "Race" and "Ethnicity" from Grants to Articles. Issue 3 (1st October 2013) - Friedman, Asia; Lee, Catherine
Abstract : The research and publication practices by which scientists produce biomedical knowledge about race and ethnicity remain largely unexamined, and most of the existing research looks at the knowledge production process at a single point in time. In light of this, we specifically focus on the questions of whether and in what ways researchers' discussions of race and ethnicity change over the course of the research process by comparing grant proposals to published articles. Using content analysis, we investigated the use of race and ethnicity in 72 grants funded by the National Cancer Institute of the National Institutes of Health between 1990 and 1999 and 144 matched articles published between 1996 and 2010, tracing the production of biomedical knowledge from study design to published findings. This is also the first study to look at whether the NIH Inclusion Mandate, which went into effect in June of 1994, changed the way investigators research and write about racial and ethnic differences. In following this knowledge production process, we explore how scientists "deliver" on their research proposal goals. In addition, we provide insight into whether and how state policies directed at guiding research practices can shape output.